Improved Liver Diffusion-Weighted Imaging at 3 T Using Respiratory Triggering in Combination With Simultaneous Multislice Acceleration. Issue 12 (December 2019) - Tavakoli, Andrej; Attenberger, Ulrike I.; Budjan, Johannes; Stemmer, Alto; Nickel, Dominik; Kannengiesser, Stephan; Morelli, John N.; Schoenberg, Stefan O.; Riffel, Philipp
Abstract : Objectives: The aim of this study was to retrospectively compare optimized respiratory-triggered diffusion-weighted imaging with simultaneous multislice acceleration (SMS-RT-DWI) of the liver with a standard free-breathing echo-planar DWI (s-DWI) protocol at 3 T with respect to the imaging artifacts inherent to DWI. Materials and Methods: Fifty-two patients who underwent a magnetic resonance imaging study of the liver were included in this retrospective study. Examinations were performed on a 3 T whole-body magnetic resonance system (MAGNETOM Skyra; Siemens Healthcare, Erlangen, Germany). In all patients, both s-DWI and SMS-RT-DWI of the liver were obtained. Images were qualitatively evaluated by 2 independent radiologists with regard to overall image quality, liver edge sharpness, sequence-related artifacts, and overall scan preference. For quantitative evaluation, signal-to-noise ratio was measured from signal-to-noise ratio maps. The mean apparent diffusion coefficient (ADC) was measured in each liver quadrant. The Wilcoxon rank-sum test was used for analysis of the qualitative parameters and the paired Student t test for quantitative parameters. Results: Overall image quality, liver edge sharpness, and sequence-related artifacts of SMS-RT-DWI received significantly better ratings compared with s-DWI ( P < 0.05 for all). For 90.4% of the examinations, both readers overall preferred SMS-RT-DWI to s-DWI. Acquisition time for SMS-RT-DWI was 34% faster than s-DWI. Signal-to-noise ratio values were significantly higher for s-DWI at b50 but did not statistically differ at b800, and they were more homogenous for SMS-RT-DWI, with a significantly lower standard deviation at b50. Mean ADC values decreased from the left to right hepatic lobe as well as from cranial to caudal for s-DWI. With SMS-RT-DWI, mean ADC values were homogeneous throughout the liver. Conclusions: Optimized, multislice, respiratory-triggered DWI of the liver at 3 T substantially improves image quality with a reduced scan acquisition time compared with s-DWI.